Benefits of hybridity in organizations: Views from public, private and the third sector - Esa Hyyryläinen; Olli-Pekka Viinamäki (The International Journal of Management Science and Information Technology (IJMSIT), 2011)
We have recently seen research examining the origin and functioning of hybrid organizations. The growing practical and academic interest in hybrids is a clear manifestation of the changing and blurring roles of governments and private sector organizations. It also reveals new ways of thinking about governments' relations with various commercial and community organizations as well as ways of reorganizing service delivery and production. While there is a growing body of research and practical knowledge, there are still significant gaps in definitions and understanding of the hybrid organization. It also constitutes an ambiguous field of organizing and leadership. This article represents a variety of definitions and approaches to the hybrid organization and addresses the particular challenges for structuring and managing the hybrids. We also put forward six measures which foster getting benefits and favorable outcomes from the hybrid organization.
Keywords: 650; Organization; hybrid; hybridization; governance; public organization; private organization